TUJUAN PENDIDIKAN ISLAM DALAM PERSPEKTIF FILSAFAT UPAYA MEMBANGUN MANUSIA PARIPURNA - Siti Apriani Hasibuan; Yuliana Siregar (Yayasan Baitul Hikmah al-Zain, 2026)
This research is motivated by the need to re-understand the goals of Islamic education from a philosophical perspective, particularly in the effort to develop complete human beings with holistic character. The main problem of this research is the lack of a comprehensive understanding of the goals of Islamic education from a philosophical perspective, especially in forming complete human beings who are balanced in spiritual, intellectual, and moral aspects. This research aims to re-explain how philosophy views the goals of Islamic education and how this concept can be applied to contemporary education. The method used is a literature study by reviewing the books and writings of classical and modern Islamic educational thinkers. Data were obtained from the thoughts of figures such as Al-Ghazali, Ibn Miskawayh, and Syed Muhammad Naquib al-Attas, supplemented by the latest educational literature. The results of this study indicate that the goal of Islamic education is essentially to shape good, knowledgeable, moral, and capable human beings who are able to live lives based on Islamic values. Education emphasizes not only knowledge, but also the development of the soul, character, and strengthening of faith. In conclusion, a philosophical perspective helps provide a more complete picture of the goals of Islamic education so that it can be used as a basis for developing education that is relevant to the needs of the times without abandoning religious values.